Information technology governance on public sector audit performance - Veerankutty, Farida; Ali, Noor Azman (Institute for Strategic and Sustainable Accounting Development, Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia, 2016)
The fast growing trend of information technology (IT) transformation in the organisation and huge IT investment by Malaysian Government have triggered the significance of IT risk and its related controls. Besides, technology-enabled auditing and IT oriented audit procedures have become crucial when performing audit task in an electronic environment. Technology-enabled auditing is a process of examination using audit technology in assuring the electronic data being managed properly and reliable in assisting auditors to form an audit opinion. Although, many initiatives being implemented to improve technology usage but audit technology usage among the auditors are still low and auditors are not attaining sufficient progress in the use of technology. This implies that technology-enabled audit performance may not lead to the expected outcomes in achieving the effective, efficient and quality audit task. Furthermore, it also indicates that the current strategies and policies may not effectively support the technology implementation. In the same vein, the under-utilisation of technologies was reported due to inadequate governance. Known the high cost and low success rate, reasons for these issues need to be understood and strategies towards success vital to be discovered. Thus, this study intent to investigate the impact of IT governance on technology enabled audit performance. IT governance is a mechanism to stimulate anticipated behaviour in the use of technology among the employees of an organisation and it is a subset of corporate governance. Agency theory will be employed in explaining the phenomena. A survey using closed-ended questionnaire will be distributed to approximately 300 Malaysia public sector auditor in National Audit Department of Malaysia whom performing technology enabled auditing. The finding of the study expected to enrich the existing body of knowledge and accounting professional practice on the significant role of IT governance in assuring the successful implementation of technology enabled auditing.